2018
DOI: 10.1071/an16592
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of genetic selection for environmental impact traits on economically important traits in dairy cows

Abstract: The authors advise that during the study period the definition (not the evaluation) of reported udder health (UDH) changed and the scale was reversed (i.e. the negative (-) associated with UDH should be positive (+) and vice versa). However, this correction was omitted in a few places in the published paper. Therefore, the correct text in the 'Expected genetic changes under selection scenarios' section should read:A relative weight of 25% of PME (selection scenario IV) generated a response of PME by -6%, MY by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
1
8
0
1
Order By: Relevance
“…Studying the effect of the introduction of MIR CH 4 trait in the breeding selection index is therefore interesting. Kandel et al (2014) studied the consequences of selection for environmental impact traits in dairy cows. The authors used CH 4 intensity (g of CH 4 per kg of milk) and calculated several approximate genetic correlations from estimated breeding values to other traits.…”
Section: Mir Spectramentioning
confidence: 99%
“…Studying the effect of the introduction of MIR CH 4 trait in the breeding selection index is therefore interesting. Kandel et al (2014) studied the consequences of selection for environmental impact traits in dairy cows. The authors used CH 4 intensity (g of CH 4 per kg of milk) and calculated several approximate genetic correlations from estimated breeding values to other traits.…”
Section: Mir Spectramentioning
confidence: 99%
“…Moraes et al (2014) identified milk fat content as a key explanatory variable for predicting CH 4 emissions of North American dairy and beef cattle. Kandel et al (2014), however, found a low negative genetic correlation between infrared-predicted MeI (calibrated from SF 6 tracer data) and fat yield (g/d; r = −0.13). Using essentially the same SF 6 tracer data, Vanlierde et al (2015) found low phenotypic correlations between fat yield (g/d) and SF 6 MeP or MeI of 0.08 and −0.13, respectively.…”
Section: Milk Production and Compositionmentioning
confidence: 99%
“…Using essentially the same SF 6 tracer data, Vanlierde et al (2015) found low phenotypic correlations between fat yield (g/d) and SF 6 MeP or MeI of 0.08 and −0.13, respectively. Additionally, Kandel et al (2014) found a moderate genetic correlation between infrared-predicted MeI (calibrated from SF 6 tracer data) and protein yield (g/d; r = −0.47). Based on same SF 6 tracer data, Vanlierde et al (2015) found low to moderate phenotypic correlations between protein yield (g/d) and SF 6 MeP or MeI of 0.53 and −0.09, respectively.…”
Section: Milk Production and Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studying the effect of the introduction of the MIR CH 4 trait in the breeding selection index is therefore interesting. Kandel et al (2014) investigated the consequences of selection for traits of environmental impact in dairy cows. These authors used methane intensity (g/kg of milk) and calculated the approximate genetic correlation from estimated breeding values.…”
Section: Indirect Phenotypesmentioning
confidence: 99%